Sistem Bagi Hasil Pengelolaan Sawah Perspektif Hukum Islam (Studi Kasus Desa Pakkanna, Kecamatan Tanasitolo, Kabupaten Wajo) - Khaerul Aqbar; Azwar Azwar; Ihwan Wahid Minu; Muh. Arfah Herwin (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2023)
This study aims to find out the review of Islamic law regarding the implementation of profit sharing in the management of rice fields in Pakkanna Village, Tanasitolo District, Wajo Regency. The type of research used is qualitative research in the form of field research with a normative and social approach. The results showed that the cooperative system for managing ricefields in Pakkanna Village used a profit-sharing system called the maruma system, in which the land owner gave his ricefields to cultivators to work on, while the seeds came from farmers. The distribution is 2:1, where 2 parts are for sharecroppers and 1 part is for landowners. Contract agreements are only made verbally, because of mutual trust. The profit-sharing system in Pakkanna Village, in Islamic law, has met the requirements because the contract is based on the Qur'an and hadith. In addition, this contract has become a custom that does not conflict with syara' and law, so the use of the profit sharing system is permissible.